An analysis of citation and research trends of Bachelor of Library and Information Science (BLIS) Theses 1996-2004 - Villanueva, Michael V.; Faderon, Rosalie B. (Quezon City Institute of Library and Information Science, University of the Philippines Diliman, 2005)
Two hundred ninety-two undergraduate theses submitted to the UPILIS during the period of 1996-2004 were analyzed to determine the present trends in research in the field of Library and Information Science (LIS) and to help in collection development and maintenance of the Institute's Library. Citation analysis was utilized to determine the characteristics of the source materials; subject analysis was done to find out the most commonly researched area and used research methodology. Descriptive statistics such as frequency and percentages were used in the analysis.
Results show that despite the advances in technology, printed materials such as books, journals and other unpublished materials such as theses and dissertations were still the most used library materials. The research trends for the nine years span of the source materials was still on Types of Libraries and Information Centers with Academic Libraries capturing the most attention from the researchers; same with Arellano's and Campanaños findings. The popularity, feasibility and accessibility of these institutions made the students prefer this category as the focus of their studies. Demanding research methods such as experimental or qualitative have little been used; the most commonly preferred research methods were still the simpler ones, such as "survey research", "observation research" and "evaluation research" as what Arellano found out. Perhaps this is because these methods can be employed cheaply by researchers working alone.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Bibliographical citations; Library science -- Research -- Philippines -- Quezon City